Can Africa Claim the 21st Century? - World Bank (Washington, DC, 2015)
Major changes are needed if Africans and their children are to claim the 21st century. With the rapidly growing population, 5 percent annual growth is needed simply to keep the number of poor from rising. Halving severe poverty by 2015 will require annual growth of more than 7 percent, along with a more equitable distribution of income. Trends in Africa will need to change radically for a catch-up process to materialize. This will require determined leadership within Africa. It will require better governance developing stable and representative constitutional arrangements, implementing the rule of law, managing resources transparently, and delivering services effectively to communities and firms. It will require greater investment in Africas people as well as measures that encourage private investment in infrastructure and production. And it will require better support and perhaps more support from the international development community. In facing these challenges, Africa has enormous potential including the potential of its women, who now provide more than half of the regions labor but lack equal access to education and factors of production. This report brings together the recent body of work particularly that emanating from Africa itself to show how some African countries are approaching common issues. African economies and sub-regions are diverse and each will have to find its way to address the challenges of the 21st century.